2021
DOI: 10.3389/fbioe.2021.761861
|View full text |Cite
|
Sign up to set email alerts
|

Coaxially Bioprinted Cell-Laden Tubular-Like Structure for Studying Glioma Angiogenesis

Abstract: Glioblastomas are the most frequently diagnosed and one of the most lethal primary brain tumors, and one of their key features is a dysplastic vascular network. However, because the origin of the tumor blood vessels remains controversial, an optimal preclinical tumor model must be established to elucidate the tumor angiogenesis mechanism, especially the role of tumor cells themselves in angiogenesis. Therefore, shell-glioma cell (U118)-red fluorescent protein (RFP)/core-human umbilical vein endothelial cell (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…It was found that 22% and 78% of the tumor CD105+ cells were human and mouse origin, respectively, suggesting that cancer cells can recruit host vascular endothelial cells to be involved in tumor angiogenesis as well as directly taking part in the angiogenesis themselves. Tubule-like forms containing endothelial/glial phenotypic cells were also detected in xenograft tumors indicating that U118 cells could transdifferentiate or fuse with endothelial cells to play a role in tumor angiogenesis (Figure E,F) …”
Section: Applications Of 3d Bioprinted Models Of Brain (Intracranial)...mentioning
confidence: 98%
See 4 more Smart Citations
“…It was found that 22% and 78% of the tumor CD105+ cells were human and mouse origin, respectively, suggesting that cancer cells can recruit host vascular endothelial cells to be involved in tumor angiogenesis as well as directly taking part in the angiogenesis themselves. Tubule-like forms containing endothelial/glial phenotypic cells were also detected in xenograft tumors indicating that U118 cells could transdifferentiate or fuse with endothelial cells to play a role in tumor angiogenesis (Figure E,F) …”
Section: Applications Of 3d Bioprinted Models Of Brain (Intracranial)...mentioning
confidence: 98%
“…Tubule-like forms containing endothelial/glial phenotypic cells were also detected in xenograft tumors indicating that U118 cells could transdifferentiate or fuse with endothelial cells to play a role in tumor angiogenesis (Figure 5E,F). 152 Glioma and GSCs promote glioma angiogenesis by converting into endothelial cells or excreting VEGF. 32 A study examined the role of GSCs in tumor vascularization on the GSC tumor model which was developed using a 3D multinozzle bioprinter.…”
Section: Applications Of 3d Bioprinted Models Of Brain (Intracranial)...mentioning
confidence: 99%
See 3 more Smart Citations